Delaying standard combined chemoradiotherapy after surgical resection does not impact survival in newly diagnosed glioblastoma patients. Issue 1 (January 2016) - Louvel, Guillaume; Metellus, Philippe; Noel, Georges; Peeters, Sophie; Guyotat, Jacques; Duntze, Julien; Le Reste, Pierre-Jean; Dam Hieu, Phong; Faillot, Thierry; Litre, Fabien; Desse, Nicolas; Petit, Antoine; et al.
Abstract: Background: To assess the influence of the time interval between surgical resection and standard combined chemoradiotherapy on survival in newly diagnosed and homogeneously treated (surgical resection plus standard combined chemoradiotherapy) glioblastoma patients; while controlling confounding factors (extent of resection, carmustine wafer implantation, functional status, neurological deficit, and postoperative complications). Methods: From 2005 to 2011, 692 adult patients (434 men; mean of 57.5 ± 10.8 years) with a newly diagnosed glioblastoma were enrolled in this retrospective multicentric study. All patients were treated by surgical resection (65.5% total/subtotal resection, 34.5% partial resection; 36.7% carmustine wafer implantation) followed by standard combined chemoradiotherapy (radiotherapy at a median dose of 60 Gy, with daily concomitant and adjuvant temozolomide). Time interval to standard combined chemoradiotherapy was analyzed as a continuous variable and as a dichotomized variable using median and quartiles thresholds. Multivariate analyses using Cox modeling were conducted. Results: The median progression-free survival was 10.3 months (95% CI, 10.0–11.0). The median overall survival was 19.7 months (95% CI, 18.5–21.0). The median time to initiation of combined chemoradiotherapy was 1.5 months (25% quartile, 1.0; 75% quartile, 2.2; range, 0.1–9.0). On univariate and multivariate analyses, OS and PFS were not significantly influenced by time intervals to adjuvant treatments. On multivariate analysis, female gender, total/subtotal resection and RTOG-RPA classes 3 and 4 were significant independent predictors of improved OS. Conclusions: Delaying standard combined chemoradiotherapy following surgical resection of newly diagnosed glioblastoma in adult patients does not impact survival.